JATI JAWA KONTRIBUSI KAYU JATI BAGI MASYARAKAT JAWA - Muhammad Zamroni (Gelar : Jurnal Seni Budaya, 2014)
Teak wood is a natural plant that thrives in Java island. People in Java, historically for a long time, have usedteak wood as the raw material of various buildings, meublelair, and the craft of carving. Teak wood givescontribution to Javanese people not only in economic aspect but also in the social, religious, art, and culturalaspects. The film â€œJava Teakâ€ is an effort to show discourse of teak wood contribution to Javanese people inorder that teak wood is placed as the important thing in the development of Javanese culture. The documentaryfilm is made by expository approach that is a documentary that directly shows the message and content ofthe film to the audience through presenter or narration in the form of text or voice.Key words: Java Teak, documentary, teak, Java, culture